Diseño e implementación de un sistema de control de velocidad para el halado de material en un banco didáctico de trefilado (2022)
Wire drawing is a process in which the cross-section of a metal bar, mainly steel or bronze, is reduced. In the industry, wire drawing is used for the realization of products used in different branches of engineering. In this work we propose the design and implementation of a control system for the material speed in a wire drawing assembly oriented to the educational field. With the design and implementation of the speed control system in the didactic wire drawing assembly, will be searched for the optimization of the process, taking into account how the wire drawing variables can affect the process, so it must be analyzed and monitored in real-time to observe their behavior.